Physical, mechanical and microstructural properties of one-part semi-lightweight geopolymers based on metakaolin modified with gypsum and lime - Shi, Jinyan; Bayraktar, Oguzhan Yavuz; Bayrak, Barıs; Bodur, Burak; Oz, Ali; Kaplan, Gokhan; Aydin, Abdulkadir Cuneyt (Elsevier BV, 2024)
The elemental composition of precursors is crucial for the performance development of geopolymers. Metakaolin (MK) was used to produce one-part geopolymers (OPG), and the influence of calcium-based components (lime and gypsum) on their properties was investigated. The experimental results show that the use of lime instead of MK increases the fluidity of the mixture, while the addition of gypsum decreases the fluidity. Meanhwlie, the use of lime to replace a small amount of MK increases the concentration of activator by consuming water and the dissolution of calcium ions also participates in the geopolymerization reaction, which enhances the mechanical properties and durability of OPG. When 10 % lime is applied, the 7-d and 28-d compressive strengths of OPG are increased by 210 % and 157.14 % compared with the plain sample, respectively. The addition of gypsum generates AFt in OPG, which reduces the compactness of the microstructure, which is not conducive to the development of the strength and durability of OPG. When 10 % gypsum is applied, the 28-d compressive and flexural strengths of OPG are decreased by 32.14 % and 26.67 % compared with plain samples, respectively. As the lime content increases, further addition of gypsum to OPG has a more negative effect on OPG due to the plundering of calcium ions in the lime. The 28-d dry density of OPG is between 1585 and 1729 kg/m3, which makes it have a lower thermal conductivity (0.87-0.94 W/m & sdot;K).